CHALLENGES AND OPPORTUNITIES ON HUMAN RESOURCE MANAGEMENT FOR ORGANIZATION DURING (COVID-19) PANDEMIC SITUATION - Sheptya Yusnta Putri; Indrayani Indrayani; Muammar Khaddafi; Ngaliman Ngaliman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to examine the challenges and opportunities during the (COVID-19) pandemic situation. In this study, we give a different view that shows how this Coronavirus affects our personal and professional lives, and how HRM (human resource management) helps their employees during this complete lockdown situation. This study is divided into three parts, the first part that shows how Coronavirus creates an opportunity for all the employees by doing their work through a digital platform or we can say that through work from home, second part show what are the challenges faced by the employees during this pandemic, and the third part is how HRM help their employees to overcome their stress as well growth of the organization. In this study, we tried to examine all the aspects during this (COVID-19) pandemic situation, also how HRM plays their role to overcome the employees stress and to balance continence in work through this entire pandemic situation.